Pengaruh Penggunaan Metode Outdoor study Terhadap Hasil Belajar IPA Siswa Sekolah Dasar - Usmansyah, Fadlil Abid; Khaeruddin; Amal, Amri (Jurnal Ilmu Pendidikan Dasar Indonesia, 2023)
This study aims to determine the description and influence of the outdoor study method on student learning outcomes in the subject of Natural Sciences at SDN 34 Libureng. Data collection techniques using direct observation, tests and documentation. The data analysis technique used in this study is the test/T-test data analysis technique. The results of this study indicate that learning using the outdoor study method influences student learning outcomes in Natural Sciences (IPA) subjects. In collecting data, research uses observation techniques, documentation and tests. The results of this study indicate that there is an influence of the outdoor study method in learning Natural Sciences. This is evidenced in the t-test table (Independent Sample Test) by obtaining a significance value of 0.006 <0.05, which means that H0 is rejected and Ha is accepted or tcount > ttable (13, 09 > 2.131).